Field notes contributed by David L. Dankert, fall 1993 - Dankert, David L.et al (1993)
Fall report of birds found in Linn County and Johnson County contributed by David L. Dankert. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1993. Plustek - flatbed